Cross sectional echocardiographic identification of hypoplastic left heart syndrome and differentiation from other causes of right ventricular overload. Issue 6 (June 1990) - Ludman, P; Foale, R; Alexander, N; Nihoyannopoulos, P
Abstract : To identify the echocardiographic features that can be used to distinguish between hypoplastic left heart syndrome and other causes of right ventricular overload in the sick neonate cross sectional echocardiographic studies of 10 neonates with hypoplastic left heart syndrome were analysed and compared with those in 15 neonates with other causes of right ventricular overload and 15 normal controls. Left ventricular and right ventricular cavity dimensions and the shape and size of the mitral valve annulus and aortic root were recorded and presented both as absolute values (mm) and corrected for body surface area (mm/m2). Logistic regression was used to produce a classification rule to estimate the probability of a neonate having hypoplastic left heart syndrome. The diameter of the mitral valve annulus was the single most discriminative variable. There was, however, considerable overlap of all the calculated features between neonates with hypoplastic left heart syndrome and those with other causes of right ventricular overload. The diagnosis of hypoplastic left heart syndrome should not be based on any one single echocardiographic feature but the general appearance of abnormal left heart valves, small cavity dimensions, and the size of the mitral valve annulus.